APPLICATION OF THE PROBLEM-SOLVING LEARNING MODEL TO IMPROVE LEARNING OUTCOMES IN IPAS LEARNING IN GRADE IV STUDENTSSD N MATARAM - Jecelind Cheril Talitha Rahma (Teaching and General Education Studies, 2025)
This research aims to improve student learning outcomes in science subjects through the application of the problem-solving learning model in grade IV of SDN Mataram. The main problem in this study is explicitly formulated as: "Can the application of the problem-solving learning model significantly improve the learning outcomes of science students in grade IV of SDN Mataram?". The method used is a pseudo-experiment with a one-group pre-test and post-test design. The research sample was 20 students in grade IV. The data collection instrument is in the form of a multiple-choice objective test. The results of data analysis showed a significant increase between the average score of pre-tests (50.40) and post-tests (85.40), with the level of learning completeness increasing from 0% to 90%. This finding confirms that the problem-solving learning model is effective in enhancing students’ science learning outcomes in primary education settings. This research has practical implications for teachers in choosing active learning models that increase student participation and academic implications in enriching empirical references related to the effectiveness of the problem-solving model in primary education. We recommend further research to apply this model to other subjects and larger populations.